National reading tests in Denmark, Norway, and Sweden: A comparison of construct definitions, cognitive targets, and response formats. (January 2017) - Tengberg, Michael
Reading comprehension tests are often assumed to measure the same, or at least similar, constructs. Yet, reading is not a single but a multidimensional form of processing, which means that variations in terms of reading material and item design may emphasize one aspect of the construct at the cost of another. The educational systems in Denmark, Norway, and Sweden share a number of traits, and in the recent decade, the development of national test instruments, especially for reading, has been highly influenced by international surveys of student achievement. In this study, national tests of L1 reading comprehension in secondary school in the three Scandinavian countries are compared in order to reveal the present range of diversity/commonality within the three test domains. The analysis employs both qualitative and quantitative aspects of data, including frameworks, text samples, task samples, and scoring guidelines from 2011 to 2014. Findings indicate that the three tests differ substantially from each other, not only in terms of the intentional and operative constructs of reading to be measured, but also in terms of testing methods and stability over time. Implications for the future development of reading comprehension assessment are discussed.